A new and unusual amphistomatic species of Tibouchina (Melastomeae, Melastomataceae) from Brazil - Guimarães, Paulo José Fernandes; Woodgyer, Elizabeth M. (Phytotaxa, 2016)
Tibouchina rosanae, a new species of Melastomataceae (Melastomeae) from the state of Mato Grosso, Brazil, is described, illustrated and compared to its putative closest allied. It is characterized mainly by the inflorescence that is lax. Tibouchina rosanae is an amphistomatic species, and the presence of stomata on the adaxial leaf surface is reported here for the first time in the genus.